2009
DOI: 10.5433/1679-0359.2009v30n1p39
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da variação sazonal no potencial alelopático de Sálvia

Abstract: ResumoA biossíntese e o acúmulo dos compostos químicos que conferem a característica alelopática em Salvia officinalis L. (Lamiaceae) são resultantes do metabolismo secundário do vegetal. O presente trabalho teve como objetivo analisar os efeitos alelopáticos de extratos aquosos de folhas frescas de Sálvia coletadas durante as estações do ano, obtidos por decocção, maceração estática, infusão e trituração sobre a germinação e o desenvolvimento de plântulas de alface (Lactuca sativa L.), totalizando 20 tratamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…Many medicinal species have been tested for their allelopathic effect, among them Leucaena leucocephala (Lam.) (Prates et al 2000), Cymbopogon citratus (DC) Stapf., Stevia rebbaudiana (Bert) (Souza et al 2005), Arctium minus (Hill) Bernh (Belinelo et al 2008), Solanum lycocarpum A. St-Hil, Solanum subumbellatum Vell., Solanum granuloso-leprosum Dunal (Oliveira 2009), Ruta graveolens L. (De Feo et al 2002), Salvia officinalis L. (Viecelli and Cruz-Silva 2009), and Vernonia tweediana Baker (Olguin et al 2005).…”
mentioning
confidence: 99%
“…Many medicinal species have been tested for their allelopathic effect, among them Leucaena leucocephala (Lam.) (Prates et al 2000), Cymbopogon citratus (DC) Stapf., Stevia rebbaudiana (Bert) (Souza et al 2005), Arctium minus (Hill) Bernh (Belinelo et al 2008), Solanum lycocarpum A. St-Hil, Solanum subumbellatum Vell., Solanum granuloso-leprosum Dunal (Oliveira 2009), Ruta graveolens L. (De Feo et al 2002), Salvia officinalis L. (Viecelli and Cruz-Silva 2009), and Vernonia tweediana Baker (Olguin et al 2005).…”
mentioning
confidence: 99%
“…Fluctuation between stimulatory and inhibitory responses, depending on the extraction methods and the extract concentration, has also been observed by Pelegrini and Cruz-Silva (2012) in Coleus barbatus (A.) Benth extracts, and by Viecelli and Cruz-Silva (2009) in Salvia officinalis L. extracts. A stimulatory effect on the initial development of lettuce has also been reported as a result of treatment with Eugenia dysenterica Mart.…”
Section: Resultsmentioning
confidence: 85%
“…The results are presented in Table 2. jas.ccsenet. Viecelli and Cruz-Silva (2009) found that different dosages of aqueous extract of Salvia officinalis L. leaves, interfered significantly in the variable SGI and the initial development of lettuce seedlings submitted to the high concentrations of the extract. Silva et al (2015) analyzing extracts of leaves of the species of the Lamiaceae's family, verified that aqueous extracts made from Mentha sp.…”
Section: Resultsmentioning
confidence: 94%